Perilaku Konsumen Produk Halal dalam Kerangka Maqashid Syariah: Integrasi TPB, Life Style, dan Health Consciousness - Latifah, Siti Nur (Moderasi : Journal of Islamic Studies, 2025)
This study aims to analyze the application of the Theory of Planned Behavior, Lifestyle, and Health Consciousness to Consumer Behavior in halal products, with Intention as an intervening variable (Study on Millennial Generation Consumers). The research employs Path Analysis, and hypothesis testing was conducted using IBM SPSS Version 25.0. The results of the first path analysis show that the Health Consciousness variable has a direct and significant influence on Intention. This finding aligns with the objectives of Maqāṣid al-Sharī‘ah, particularly ḥifẓ al-nafs (protection of life), as health awareness encourages consumers to choose products that are safe, healthy, and halal to preserve their well-being and quality of life. Meanwhile, the variables Attitude, Subjective Norms, Perceived Behavior Control, and Lifestyle have direct but insignificant effects on Intention. The second path analysis indicates that Subjective Norms and Intention have a direct and significant influence on Consumer Behavior. This corresponds to Maqāṣid al-Sharī‘ah, especially ḥifẓ al-dīn (protection of religion) and ḥifẓ al-‘aql (protection of intellect), as social norms within Muslim communities are often shaped by Islamic values that encourage consumption behaviors aligned with halal and ṭayyib principles. Conversely, Attitude, Perceived Behavioral Control, Lifestyle, and Health Awareness show direct but insignificant effects on Consumer Behavior. In the indirect effect pathway, Health Awareness influences Intention and subsequently impacts Consumer Behavior among millennial consumers of halal-labeled health drinks. This result is also consistent with Maqāṣid al-Sharī‘ah, as health awareness leading to the choice of halal, healthy, and safe products supports the preservation of life (ḥifẓ al-nafs) and intellect (ḥifẓ al-‘aql). Moreover, choosing halal products reflects the proper and beneficial use of wealth (ḥifẓ al-māl), ensuring consumption practices guided not merely by lifestyle preferences but by individual and societal well-being.